Spatial cross-regressive models in the study of the spatial diffusion of innovation in Central Europe - Kisiała, Wojciech (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
In the paper, spatial cross-regressive models were used for the identification of the processes of the spatial diffusion of innovations in Central Europe. As it is difficult to measure the diffusion of innovations directly, the empirical part of the work was based on symptomatic indicators. In the course of the research, the author undertook to show how variables indicating the level of innovation (considered to be independent variables) shaped the efficiency of work, expressed as the indicator of gross value added per worker (modelled dependent variable). The regression analysis conducted showed that there was a statistically significant link between innovation and the efficiency of work in Central European countries, also in the dimension of spatial interactions among regions. Econometric modelling led to the conclusion that the spatial diffusion of innovations occurred
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 97-105
Keywords: diffusion of innovation; spatial econometrics; spatial cross-regressive models; NUTS2 regions; Central Europe; dyfuzja innowacji; ekonometria przestrzenna; modele regresji krzyżowej; regiony NUTS2; Europa Środkowa